Planet‐Wide Ozone Destruction in the Middle Atmosphere on Mars During Global Dust Storm. Issue 11 (2nd June 2022) - Daerden, F.; Neary, L.; Wolff, M. J.; Clancy, R. T.; Lefèvre, F.; Whiteway, J. A.; Viscardy, S.; Piccialli, A.; Willame, Y.; Depiesse, C.; Aoki, S.; Thomas, I. R.; et al.
Abstract: The Nadir and Occultation for MArs Discovery (NOMAD)/UV‐visible (UVIS) spectrometer on the ExoMars Trace Gas Orbiter provided observations of ozone (O3 ) and water vapor in the global dust storm of 2018. Here we show in detail, using advanced data filtering and chemical modeling, how Martian O3 in the middle atmosphere was destroyed during the dust storm. In data taken exactly 1 year later when no dust storm occurred, the normal situation had been reestablished. The model simulates how water vapor is transported to high altitudes and latitudes in the storm, where it photolyzes to form odd hydrogen species that catalyze O3 . O3 destruction is simulated at all latitudes and up to 100 km, except near the surface where it increases. The simulations also predict a strong increase in the photochemical production of atomic hydrogen in the middle atmosphere, consistent with the enhanced hydrogen escape observed in the upper atmosphere during global dust storms. Plain Language Summary: Global dust storms are rare but impactful events on Mars, occurring about once in a decade. Previous investigations found how water vapor is redistributed throughout the entire atmosphere in a dust storm. Photolysis of water vapor by sunlight produces highly reactive species that destroy ozone (O3 ). Here we present O3 measurements taken by the NOMAD/UVIS instrument on the ExoMars Trace Gas Orbiter in the 2018 global dust storm. After advanced data filtering, they demonstrate how O3 in the middle atmosphere was much reduced compared to one Mars year later when no dust storm occurred. 3D atmospheric model simulations of atmospheric chemistry in the global dust storm confirm this planet‐wide O3 destruction, and help to understand the involved processes. The simulations also predict a strong increase in production of atomic hydrogen in the middle atmosphere, that can explain the observed increased hydrogen atmospheric escape during global dust storms. Key Points: NOMAD ozone (O3 ) data filtering during the 2018 global dust storm shows strong O3 destruction compared to one year later with no dust storm 3D simulations of atmospheric chemistry in the 2018 global dust storm are presented to understand impact on odd hydrogen and odd oxygen The model confirms middle‐atmospheric O3 destruction in the dust storm and predicts increased photochemical production of hydrogen